Voluntary wheel running in mice increases the rate of neurogenesis without affecting anxiety-related behaviour in single tests - Garrett, Lillian; Lie, Dieter Chichung; De Angelis, Martin Hrabe; Wurst, Wolfgang; Hoelter, Sabine M. (BMC Neuroscience, 2012)
The role played by adult neurogenesis in anxiety is not clear. A recent study revealed a surprising positive correlation between increased anxiety and elevated neurogenesis following chronic voluntary wheel running and multiple behavioural testing in mice, suggesting that adult hippocampal neurogenesis is involved in the genesis of anxiety. To exclude the possible confounding effect of multiple testing that may have occurred in the aforementioned study, we assessed (1) the effects of mouse voluntary wheel running (14 vs. 28 days) on anxiety in just one behavioural test; the open field, and (2), using different markers, proliferation, differentiation, survival and maturation of newly born neurons in the dentate gyrus immediately afterwards. Effects of wheel running on anxiety-related behaviour were confirmed in a separate batch of animals tested in another test of anxiety, the light/dark box test.Running altered measures of locomotion and exploration, but not anxiety-related behaviour in either test. 14 days running significantly increased proliferation, and differentiation and survival were increased after both running durations. 28 day running mice also exhibited an increased rate of maturation. Furthermore, there was a significant positive correlation between the amount of proliferation, but not maturation, and anxiety measures in the open field of the 28 day running mice.Overall, this evidence suggests that without repeated testing, newly born mature neurons may not be involved in the genesis of anxiety per se.
EVALuna2:4683